Neuroprotective and anticonvulsant effect of trimetazidine in a PTZ-kindling model of mice through modulation of the IL-1β/IL-1R1 and HMGB-1/TLR-4 axis - Ahmad, Shahnawaz; Samim, Mohammed; Jain, Seema; Vohora, Divya; Nidhi (Frontiers in Pharmacology, 2025)
BackgroundEpilepsy is a chronic and complex brain disorder characterized by frequent seizures, cognitive impairments, neuroinflammation, oxidative stress, and imbalances in neurotransmitters. Developing an effective therapeutic intervention to target these pathological interventions remains a challenge. Trimetazidine (TMZ), the most commonly known anti-ischemic agent, has emerged as a promising candidate for its role in epilepsy due to its diverse mechanisms of action. This study investigates the neuroprotective, anticonvulsant, anti-inflammatory, antioxidant, and neuromodulatory effects of TMZ in managing epilepsy.MethodsKindling was induced by administering Pentylenetetrazole (30 mg/kg, i.p) to Swiss albino mice on every alternate day; TMZ (5, 10, and 20 mg/k p.o) or sodium valproate (200 mg/kg p.o) was given for 5 weeks. Seizure severity was assessed on the Racine scale, and cognitive function and learning were evaluated using the elevated plus maze and the passive avoidance apparatus. Muscle strength was measured using the rotarod test. Neuroinflammatory biomarkers (IL-1β, IL-1R1, IL-6, NF-κB, TNF-α, HMGB-1, TLR-4), oxidative stress markers (MDA, GSH, SOD, catalase), and neurotransmitter (GABA, glutamate, dopamine, serotonin) levels were estimated in the hippocampus and cerebral cortex using commercially available sandwich ELISA kits.ResultsTMZ, primarily at 10 and 20 mg/kg, significantly reduced seizure scores and improved the transfer latency, step-down latency, and motor abilities in the PTZ-kindled animals. It significantly reduced proinflammatory molecules IL-1β, IL-1R1, IL-6, NF-κB, TNF-α, HMGB-1, TLR-4. Additionally, it increased antioxidant enzyme activity (GSH, SOD, catalase) while lowering MDA levels and restoring GABA, dopamine, and serotonin levels, as well as suppressing glutamate levels, comparable to VPA at 200 mg/kg/day p.o.ConclusionTMZ, at doses of 10 and 20 mg/kg p.o., demonstrated anticonvulsant and antioxidant activity, suppressed kindling progression, and restored neurotransmitter balance. Furthermore, TMZ has shown anti-inflammatory activity against neuroinflammation during epilepsy.